(untitled) (Sebha University Conference Proceedings, 2024)
There are different ways of minimizing the emission of CO2 resulting from different industrial based of using fossil fuel. Nowadays, the alternative methods for producing energy also are developed. One ways is to use hydrogen as a source of electricity which is generated from mixing hydrogen with oxygen via the electrochemical process. The current work is dealing with the factors that affect the amount of hydrogen production, such as voltage and amperage Two different electrolytes were employed in this work (NaOH & KOH) to evaluate the H2 production levels. Two ways used for characterizing the stability of electro-catalysts to produce hydrogen via the electrolysis. One is the relationship (I–t curve) which measures the current variation with time under a fixed potential. In this way, the results showed that the changes in H2 production values at different currents in both NaOH and KOH was observed. The changes may attribute to the conductivity of the electrolysis. The other ways for characterizing hydrogen production via the electrolysis is applied the relationship (E–t curve) to measure the potential change with time at a fixed current. Here, the rate of hydrogen production decreased as voltage increased in both electrolyte mediums. This result explained in terms of overvoltage created over the electrode surface.